A son in heaven, but no father on earth: A note in the margin of a "Tale of Two Kings" - Verheyden, Joseph (HTS teologiese studies, 2011)
The article is meant to offer a comment on the thesis of Andries G. van Aarde about the socalled fatherlessness of Jesus. The author argues for a more critical disposition towards a historical-psychological approach of ancient texts. Jesus’ attitude towards children, which is illustrated in Mark 10:13–16, and the story of Jesus’ birth and of Herod’s reaction to it as told by Matthew, are used as test cases.